Features of the Use of Renewable Energy Sources in Agriculture - Sultanova, Z.; Bolyssov, T.; Yessengeldin, B.; Akybayeva, G.; Zhanseitov, A. (My University, 2019)
The article considers the prospects of using renewable energy sources in agriculture. The authors focused on the following types of renewable energy sources: Solar, biomass, wind, and hydro generated power. Based on the analysis of Renewables Global Status Report data, the authors identified a decrease in the amount of investment in renewable energy and fuel by developed countries in developing countries. This work highlights the main reasons for the development of renewable energy (environmental safety, energy independence), as well as positive and negative aspects of the transition to renewable energy. The authors of the article reveal the features of job creation in the renewable energy industries, which will compensate for the loss of jobs in the field of fossil energy. Much attention is paid to the economy of renewable energy sources, revealing the relationship between energy use and economic growth. According to the authors, the use of RES not only increase the level of energy supply to remote rural settlements, but also can have a significant positive impact on the economy of agriculture.В статье рассматриваются перспективы использования возобновляемых источников энергии в сельском хозяйстве. Авторы сосредоточились на следующих типах возобновляемых источников энергии: солнечная энергия, биомасса, энергия ветра и гидроэнергии. На основе анализа данных Доклада о состоянии возобновляемых источников энергии в мире авторы выявили уменьшение объема инвестиций в возобновляемую энергию и топливо со стороны развитых стран в развивающихся странах. В этой работе освещаются основные причины развития возобновляемых источников энергии (экологическая безопасность, энергетическая независимость), а также положительные и отрицательные аспекты перехода на возобновляемые источники энергии. Авторы статьи раскрывают особенности создания рабочих мест в отраслях возобновляемой энергетики, которые будут компенсировать потерю рабочих мест в области ископаемых источников энергии. Большое внимание уделяется экономике возобновляемых источников энергии, раскрывая взаимосвязь между использованием энергии и экономическим ростом. По мнению авторов, использование ВИЭ не только повысит уровень энергоснабжения отдаленных сельских населенных пунктов, но и может оказать существенное положительное влияние на экономику сельского хозяйства.
International Journal of Energy Economics and Policy
Keywords: экономика труда; научный журнал; возобновляемые источники энергии; периодическое издание; потеря рабочих мест; зарубежное издание; импакт-фактор 2019; дальнее зарубежье; скопус